Uso de sistema de informação geográfica (SIG) para seleção de plantas matrizes de quixabeira [Sideroxylon obtusifolium (Roem. & Schult.) T.D. Penn.] - Sá, Talita Freitas Filgueira de (2018)
Quixabeira [Sideroxylon obtusifolium (Roem. & Schult.) T.D. Penn.] is a native species of the Caatinga biome whose population has been reduced by several factors, including anthropic interference. The monitoring of the characteristics of the environment where the species is and the registry of the data obtained in the laboratory are alternatives that can contribute to the individualized decision making. For this, the current research aimed at the creation of a Geographic Information System (GIS), which relates data referring to the quality of seeds from S. obtusifolium from Boa Vista - PB. The system must generate spatial analysis of the matrices, cartographic product, multicriteria analysis and generate a model that can be reproduced for other species. The system was produced from three stages: data collection, seed analysis and modeling of GIS software. At the time of the collection, the matrix plants were located spatially by a GPS receiver and taken to the seed analysis laboratory of Universidade Federal da Paraíba/CCA. In the analysis phase, fruit and seed biometry tests, germination and vigor tests (emergence, first counting, IVG, length, dry mass of seedlings and electrical conductivity) were performed. The M04 (46%) and M07 (44%) matrices obtained the best results in the germination test. In the biometrics evaluation, the matrix M09 presented more significant results, contradicting the electrical conductivity test, when it had most of its cellular systems deteriorated. A database was generated in the Qgis software for spatial and multicriteria analysis of the matrix plants. In the multicriteria analysis all the items were consulted from the second statistical grouping and the M11 matrix was considered the most indicated as a seed producer among the sixteen studied S. obtusifolium matrices, since it presented average results between the two main groupings for the set tests. GIS is a geotechnical tool capable of establishing a relationship between S. obtusifolium seed analysis data and the observation of the environment where the matrix exists; it is a system that can be adapted to any other species as well as to other types of data.